Entrepreneurs de la migration : Des stratégies pour contourner les obstacles bureaucratiques - Sandoz, Laure (Anthropologica, 2021)
Although migrant selection by state apparatuses plays a crucial role in structuring current migration processes, to date few studies have empirically analyzed how such procedures function and are experienced when applied to categories of foreigners perceived as “desirable.” The present study attempts to fill this gap by providing an ethnographic study that sheds light on the experience and agency of the different actors involved in the selection process of highly qualified non-European nationals who wish to come and work in Switzerland. The analysis shows that access to mobility is based on a set of complex interactions involving not only prospective immigrants and state employees, but also networks of non-state institutions that see the mobility of skilled workers as a source of profit. These actors facilitate access to residence and work permits for foreigners from whom they hope to derive economic added value. However, they can also force them into situations of dependency and immobility insofar as restrictive admission systems, in Switzerland and elsewhere, make the foreigners concerned dependent on their administrative support.